Numerical analysis of the influence of press-fitting on the fatigue life of railway axle - Theingi Nwe; Monsak Pimsarn (My University, 2024)
This study investigated the influence of press-fitting on the stress concentration and fatigue life of axles. Models of finite element analysis (FEA) with and without the press-fitting effect were developed using Abaqus software. These models were used to analyze the axle strength and profile the stress histories under various loads and running conditions, such as bending load, wheel-rail contact force, lateral force, and press-fitting force. Their combined loads were responsible for the axle fracture. Also, the prediction of fatigue life was extended to a three-dimensional stress state under fully reversed cyclic loading and variable overload spectra using commercial Fe-safe software with a strain-based Brown-Miller Morrow fatigue algorithm. With the press-fitting effect, the maximum von Mises stress at the groove notch transition zone of the axle was 6% higher than without the press-fitting effect. Press-fitting reduced the fatigue life of an axle by 37% compared to the ones without press-fitting, and the most damage happened at the same node as the maximum von Mises stress.
Keywords: Mechanical stress and fatigue analysis